Estudio de prefactibilidad para la instalación de una planta productora de bebida a partir de algarrobo (Prosopis pallida), tarwi (Lupinus mutabilis) y quinua (Chenopodium quinoa) - Manrique Pasión, Maggie Lalesca (2020)
The present research project proposes a study for the installation of the production plant of a drink made from carob (Prosopis pallida), tarwi (Lupinus Mutabilis), and quinoa (Chenopodiun quinoa), with strawberry pulp destined for the Peruvian market. This 250 ml drink is low in sugar and helps improve the balance of essential amino acids in the body (FAO, s.f., p.41). The market study propose that the target audience includes people older than 3 years of age from Metropolitan Lima who belong to NSE A and B who prefer to consume natural products. In addition, it was obtained that the demand for the beverage for the year 2023 is 199 910 liters o 799 640 bottles. In the same way, a location study was carried out in which, through the factor classification analysis, the ideal location of the plant in Lurin was obtained. On the other hand, the size of the plant was determined by the size of the market and is 110 bottles per hour. Plans were also made to assure the quality and safety of the drink, maintenance plans, safety and care of the environment and design of the supply chain. Then, the area for each zone was calculated and the surface of the plant was arranged to be 420 m2. In addition, the company will have an anonymous society (S.A.C) as its corporate model and will have a general manager and 5 area managers. Finally, it was found that the project is feasible. The investment for this project is S/1 191 377, which is financed by COFIDE by 40% and own capital by 60%. It was calculated an economic NPV of S/ 90 122 and a financial NPV of S/ 179 614. In addition, it has an economic IRR of 19,73% and a financial IRR of 24,49%.